Ashura in Italy: The Reshaping of Shi'a Rituals - Mirshahvalad, Minoo (Religions, 2019)
This essay explores the impacts of Italy's socio-religious tendencies on the Shi'a rituals of Muḥarram and Ṣafar. Ethnography and semi-structured interviews were the main methods adopted for the performance of this research. The implications of commemorating the Karbala tragedy in Italy were studied from four viewpoints. This article demonstrates that the presence of Shi'as in Italy not only exerts an effect on the core meaning of these rituals, namely paying tribute to ?usayn's courageous stand against injustice, but also on the structure of Shi'a communities in terms of gender relations and power hierarchy.